Bioresources technology in sustainable agriculture : biological and biochemical research - Abdullah, Mohamad Faiz Foong; Ali, Mohd Tajudin Bin Mohd; Yusof, Farida Zuraina M. (Waretown, NJ : Apple Academic Press, 2017)
This book focuses on cutting-edge advances and applications in tropical agriculture and bioresources. It outlines some of the newest advances, basic tools, and the applications of novel approaches to improve agricultural practices and utilization of bioresources for the enhancement of human life. Highlights include a thorough discussion on various aspects of agricultural modernization through technological advances in information technology, efficient utilization of under-exploited natural bioresources, new chemical approaches for the generation of novel biochemicals, and the applications of forensic and genetics approaches for bioresource conservation.
part, Technological Advances for Sustainable Agricultural Practices -- chapter 1 A Fuzzy approach to categorizing ripeness of citrus suhuensis using selected optical indices / Noor Aishah khairuzzaman Hadzli Hashim Noor Ezan abdullah Mohd Suhaimi sulaiman Azrie Faris mohd azmi Ahmad Faiz mohd sampian -- chapter 2 Automated visible color spectrum model for recognizing ripeness of citrus suhuiensis / Faridatul Aima Ismail Hadzli Hashim Nina Korlina Madzhi Noor Ezan Abdullah Nurul Hanani Remeli -- chapter 3 Effect of temperature on the life performance of tropical cladoceran, ceriodaphnia cornuta from tasik elham, perlis / Roslinda Binti ismail Hasnun Nita binti ismail Tay Chia chay -- chapter 4 Semantic multi-modality ontology image retrieval with relevance feedback for herbal medicinal plants / Mohd Suffian Sulaiman Sharifalillah Nordin Nursuriati Jamil -- chapter 5 Effects of diets containing effective microorganisms (EM) on growth performance, worm burden, hematological and biochemical analysis in female goats / Muhammad Anbariq Abdul Razak Muhammad Zaki Zakaria Mohd Asmawi Mohd Tayid Shamsul Bahrin Gulam Ali -- chapter 6 RFID application development for a livestock monitoring system / M. H. Ariff I. Ismail -- part, Molecular Aspect of Natural Biodiversity -- chapter 7 PV92, ACE, and TPA25 Alu insertion polymorphism in the kelantan malaysia sub-ethnic group / Azzura Abdullah Wan Nurhayati Wan Hanafi Farida Zuraina Mohd Yusof -- chapter 8 Screening and isolation of locally thermophilic facultative anaerobe bacteria for biosurfactant production / Nurul Fatihah T. Z. M. Tengku Elida A. K. Khalilah W. O. Wan Siti Atikah S. Sabiha Hanim A. Amizon -- chapter 9 Toxicity effects of dimethoate and chlorpyrifos on esterase in tilapia (oreoceromis niloticus) / Asysyuura Adytia Patar Jessey Angat Nordiana Suhada Mohamad Tahiruddin Farida Zuraina Mohd Yusof Wan Rozianoor Mohd Hassan -- chapter 10 Preliminary Study Ofhuman Earprints: Methoddevelopment On Sampling Andenhancement Technique Ofearprints On A Non-Poroussurface / Nurulfarhana Zulkifli Rumiza Abd Rashid -- chapter 11 Influence of diclofenac on development rates of forensic blowfly chrysomya megacephala / Siti Aisyah Binti Shamsuddin Nurul Farhana Binti Zulkifli Farida Zuraina Binti Mohd Yusof Khairulmazidah Binti Mohamed Rumiza Binti Abd Rashid -- part, Renewable Products from Agricultural and Natural Sources -- chapter 12 The effect of mandibular angulation on gonial angle and tooth length measurement of dental panoramic radiographs / Tong Wah Lim Budi Aslinie Md Sabri Rohana Ahmad -- chapter 13 Screening of the best carbon and nitrogen sources for pseudomonas aeruginosa as a potential polyhydroxyalkanoates (PHAs) and rhamnolipids producer / Mazni Mohd Yatim Tengku Elida Tengku Zainal Mulok Nik Roslan Nik Abdul Rashid Amizon Azizan -- chapter 14 Survivability characteristics of bifidobacterium spp. Isolates from newborn meconium and breast-fed/ formulated infant feces in acidic-simulated intestinal conditions / Yusha Farzini Mat Nor Rohana Abdul Khalil Khalilah -- chapter 15 Antioxidant and anti-bacterial potential of lichen species from malaysia / Luqman Saidi Mohd Faiz Foong Abdullah Kamsani Ngalib Wan Yunus Wan Ahmad Mohd Rozi Ahmad Asmida Ismail Muhammad Ismail Abd Kadir -- part, Sustainable Synthesis and Production of Advanced Organomaterials -- chapter 16 Synthesis Of Unnatural Amino Acids: Betulinic Acid Peptides As Bioactive Molecules / Mohd Tajudin Bin Mohd Ali Habsah Binti Zahari Siti Aisyah Binti Aliasak -- chapter 17 Synthesis Of Enantiopure Azido Trimethylsiloxy Cyclohexene Derivatives: A Useful Intermediates For The Synthesis Of Tamiflu / Mohd Tajudin Mohd Ali Siti Aisyah Aliasak Habsah Zahari Syed Abdul Illah Alyahya Syed Abdul Kadir -- chapter 18 Synthesis of amino-based metal organic framework (MOF) in oxidative catalysis / Karimah Kassim Siti Nurhazlin Jaluddin Wan Nazihah Wan Ibrahim -- chapter 19 Conductivity studies of schiff base ligands derived from phenylenediamine derivatives / Karimah Kassim Muhamad Faridz Osman.
Keywords: Agricultural biotechnology -- Research; Agricultural resources -- Research